An Evaluation of Water Pollution in the Southern Iraqi Marshes by Using Bacterial Indicators and Other Related Parameters - Mohammed Fadhil Abo-Ksour (Journal of Global Pharma Technology, 2017)
Seven selected stations were chosen in Al-Hammer marshes in the south of Iraq. The stations were chosen to cover this big area on this natural lake starting from Mneba, Omria, Jzera, Tar, Sweha, as well as two stations were near to Chebaesh which namelyNC1 and NC2. The samples collection was done in the first day of three months; June, July, and August 2016.Water physical and chemical characteristics such as temperature, pH, salinity, and dissolved oxygen (DO) were analyzed. In addition, total bacterial concentration, total coli form, fecal coli form, streptococci and fecal streptococci were determined by the serial dilution technique using Most Probable Number method (MPN) and Total Bacterial Count (T.B.C). The results show that the averages of temperature, pH, salinity, and DO were 34.5°, 7.5, 1.28 ppm, 1.04 mg/respectively. The results bacterial detections showed that total bacterial count (T.B.C). We’re ranging from 1*105 /dl to 2*107 /dl with average equal to 2.4*106 /ml, while fecal coli form (FC) were ranging from 300 /dl to 5*104 /dl with average equal to 7*103 /dl, as well fecal streptococci (FS) average was 1000 /dl and the results were ranging from 100 /dl till it reaches to 5000 /dl, with average around1000 /dl. FC/FS ratio were ranging from 1to 40 and both of them were recorded in June with average of the whole stations equal to 10.9, The highest FC/FS average among all the selected stations was in Jzera (28.9), while the lowest one was in Sweha (1.8).However, FC/FS ratios in Jzera, Sweha and Mneba stations were <4, while they were >4 in the other stations. Keywords: Iraqi marches, Dissolved oxygen, Salinity, Fecal coli form, Fecal streptococci, FC/FS ratio.